Redescription of Mesoschendyla javanica (Attems, 1907) and its first records from Borneo (Chilopoda, Geophilomorpha, Schendylidae) - George Popovici; Nesrine Akkari; Gregory Edgecombe (Biodiversity Data Journal)
The geophilomorph Mesoschendyla javanica (Attems, 1907) was originally described from a small number of males collected from bat guano in Tjompea (Ciampea), Java. Subsequently, no additional material was identified. The type series remained the only specimens belonging to this genus known from Asia.Mesoschendyla javanica is re-discovered 118 years after its original description amongst centipedes collected from soil cores taken during the 1977–1978 Royal Geographical Society Gunung Mulu Expedition to Sarawak (Borneo, East Malaysia) and is deposited in the collection of the Natural History Museum (London). The new material comprising 49 specimens, amongst which are the first known females, is described and illustrated, shedding light on intraspecific morphological variation. The syntypes and sole previously available specimens are redescribed and illustrated, completing the summary original description of the species. Ecological and biogeographical notes are provided for Sarawak specimens.